2004
DOI: 10.1213/01.ane.0000134800.46276.21
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Factor XIII Availability for Thrombin and Early Loss of Clot Firmness in Patients with Unexplained Intraoperative Bleeding

Abstract: To explore relevant changes in unexplained intraoperative bleeding, we evaluated elements of the final steps of the coagulation cascade in 226 consecutive patients undergoing elective surgery. Patients were stratified for the occurrence of unexplained intraoperative bleeding according to predefined criteria. Twenty patients (8.8%) developed unexplained bleeding. The median intraoperative blood loss was 1350 mL (bleeders) and 400 mL (nonbleeders) (P < 0.001). Fibrinogen and Factor XIII (F. XIII) were more rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
13

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 15 publications
4
92
1
13
Order By: Relevance
“…Increased soluble fibrin monomers and decreased factor XIII activity were found among elective surgical patients with unexpected bleeding [76]. In patients with a factor XIII activity of ≤60% undergoing neurosurgery the relative risk of developing a postoperative hematoma was 6.4-fold.…”
Section: Management Of Hepatic Coagulopathymentioning
confidence: 99%
“…Increased soluble fibrin monomers and decreased factor XIII activity were found among elective surgical patients with unexpected bleeding [76]. In patients with a factor XIII activity of ≤60% undergoing neurosurgery the relative risk of developing a postoperative hematoma was 6.4-fold.…”
Section: Management Of Hepatic Coagulopathymentioning
confidence: 99%
“…In some clinical studies, an increased tendency to bleed has been observed in surgical patients even at factor XIII activities of below 60 per cent 56,70,71 . There is as yet insufficient evidence to show the extent of blood loss needed to trigger a critical decrease in factor XIII.…”
Section: Factor XIIImentioning
confidence: 99%
“…Aussagen bejaht werden können, dann kann vom Vorliegen einer neu aufgetretenen Koagulopathie ausgegangen werden. Dieser validierte [2] Ansatz erlaubt eine strukturierte klinische Diagnose einer erworbenen intraoperativen Koagulopathie.…”
Section: Definition Und Quantifizierung Von Intraoperativen Blutungenunclassified
“…Auch hier scheint die Wahl der adäquaten Thromboseprophylaxe wichtig, um Blutungskomplikationen gering zu halten [36]. Bei Patienten mit ansonsten unerklärter intraoperativer Koagulopathie gibt es Hinweise darauf, dass der relative Verlust der Vernetzungskapazität durch Verlust von Faktor XIII (im Vergleich zur Menge an gebildetem Prothrombin) zu einem frühen Verlust der Gerinnselfestigkeit und damit zu einem erhöhten Blutverlust [2,37] führt. Unsere Erfahrungen zeigen, dass der perioperative, erworbene Faktor-XIII-Mangel ein häufiges Phänomen ist [38].…”
Section: Unterschiedliche Pathophysiologische Hintergründe Von Koagulunclassified
See 1 more Smart Citation